Radiation dosimetry of 68Ga-PSMA-11 (HBED-CC) and preliminary evaluation of optimal imaging timing - Afshar-Oromieh, Ali; Kratochwil, Clemens; Giesel, Frederik L.; Haberkorn, Uwe (European journal of nuclear medicine and molecular imaging, 2016)
PurposeThe clinical introduction of 68Ga-PSMA-11 (“HBED-CC”) ligand targeting the prostate-specific membrane antigen (PSMA) has been regarded as a significant step forward in the diagnosis of prostate cancer (PCa). In this study, we provide human dosimetry and data on optimal timing of PET imaging after injection.MethodsFour patients with recurrent PCa were referred for 68Ga-PSMA-11 PET/CT. Whole-body PET/CTlow-dose scans were conducted at 5 min, and 1, 2, 3, 4 and 5 h after injection of 152-198 MBq 68Ga-PSMA-11. Organs of moderate to high uptake were used as source organs; their total activity was determined at all measured time points. Time-activity curves were created for each source organ as well as for the remainder. The radiation exposure of a 68Ga-PSMA-11 PET was identified using the OLINDA-EXM software. In addition, tracer uptake was measured in 16 sites of metastases.ResultsThe highest tracer uptake was observed in the kidneys, liver, upper large intestine, and the urinary bladder. Mean organ doses were: kidneys 0.262 ± 0.098 mGy/MBq, liver 0.031 ± 0.004 mGy/MBq, upper large intestine 0.054 ± 0.041 mGy/MBq, urinary bladder 0.13 ± 0.059 mGy/MBq. The calculated mean effective dose was 0.023 ± 0.004 mSv/MBq (=0.085 ± 0.015 rem/mCi). Most tumor lesions (n = 16) were visible at 3 h p.i., while at all other time points many were not qualitatively present (10/16 visible at 1 h p.i.).ConclusionsThe mean effective dose of a 68Ga-PSMA-11 PET is 0.023 mSv/MBq. A 3-h delay after injection was optimal timing for 68Ga-PSMA-11 PET/CT in this patient cohort.